The Potential of Modified Cassava Flour (MOCAF) as a Low Glycemic Index Functional Food for the Prevention and Management of Diabetes Mellitus: A Literature Review: Wiwi Febriani ,Ramadhana Komala - Wiwi Febriani Febriani (Fakultas Kedokteran, 2026)
Diabetes mellitus is a chronic metabolic disease whose prevalence continues to increase and has become a major global public health challenge. Dietary management through the consumption of low-glycemic-index foods is considered an important strategy for the prevention and control of diabetes mellitus. Modified Cassava Flour (MOCAF) is a fermented cassava flour with improved physicochemical and functional properties compared to conventional cassava flour. This article aimed to review the potential of MOCAF as a low-glycemic-index functional food for the prevention and management of diabetes mellitus. The study employed a literature review approach by examining scientific publications related to MOCAF characteristics, glycemic index, resistant starch, and their associations with glucose metabolism. The findings indicate that MOCAF contains resistant starch and slowly digestible starch, which may reduce glycemic response, improve insulin sensitivity, and support blood glucose regulation. Furthermore, MOCAF has promising potential as a local food alternative to support food diversification and diabetes prevention programs. However, further clinical studies are required to strengthen the evidence regarding the effectiveness of MOCAF in diabetes management.